2012
DOI: 10.1037/a0026413
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, advice, and the ability to discern: Feeling anxious motivates individuals to seek and use advice.

Abstract: Across 8 experiments, the influence of anxiety on advice seeking and advice taking is described. Anxious individuals are found to be more likely to seek and rely on advice than are those in a neutral emotional state (Experiment 1), but this pattern of results does not generalize to other negatively valenced emotions (Experiment 2). The relationships between anxiety and advice seeking and anxiety and advice taking are mediated by self-confidence; anxiety lowers self-confidence, which increases advice seeking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
218
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 215 publications
(232 citation statements)
references
References 111 publications
(119 reference statements)
7
218
1
2
Order By: Relevance
“…Participants in the neutral condition wrote about how they typically spend their evenings (Gino et al, 2012). Prior research has shown that this type of autobiographical recall task is a valid 1 Across experiments, preliminary analyses revealed no moderation by participant gender.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Participants in the neutral condition wrote about how they typically spend their evenings (Gino et al, 2012). Prior research has shown that this type of autobiographical recall task is a valid 1 Across experiments, preliminary analyses revealed no moderation by participant gender.…”
Section: Methodsmentioning
confidence: 86%
“…means of inducing specific incidental emotions (e.g., Bodenhausen et al, 1994;Dunn & Schweitzer, 2005;Tiedens & Linton, 2001), including anxiety-related states (e.g., Gino et al, 2012;Kuhbandner & Zehetleitner, 2011;Lerner & Keltner, 2001;Marzillier & Davey, 2005;Whitson et al, 2015;see Lench, Flores, & Bench, 2011, for a meta-analysis), that have carry-over effects on subsequent judgments and behaviors. Spatial perspective-taking task.…”
Section: Methodsmentioning
confidence: 99%
“…These effects are mediated by low negotiator self-efficacy (Brooks & Schweitzer, 2011). Similarly, anxious individuals seek out and rely more heavily on advice, even when the advice is obviously bad, because they do not feel confident in their own ability to make good judgments (Gino et al, 2012).…”
Section: Anxietymentioning
confidence: 99%
“…Individuals who feel anxious tend to focus on the potential negative outcomes of future events and believe that those outcomes are more likely to occur (Lerner & Keltner, 2001;Raghunathan & Pham, 1999). Those beliefs lead anxious individuals to have lower self-confidence, to be more risk-averse than individuals in a neutral state, and to struggle with cognition immediately before and during performance tasks (e.g., Eysenck, 1992;Gino et al, 2012). In contrast, individuals in an excited state tend to focus on the potential positive outcomes of upcoming events and believe that they can achieve more positive outcomes (Ashby, Isen, & Turken, 1999;Aspinwall & Taylor, 1997;Brown & Curhan, 2013;Fredrickson, 2001;Jamieson et al, 2010;Scheier, Weintraub, & Carver, 1986;Schnall, Roper, & Fessler, 2010).…”
Section: Reappraising Anxiety As Excitementmentioning
confidence: 99%
See 1 more Smart Citation